Physical and Chemical Research in Velebita Pit (Croatia) - Paar, Dalibor; Ujević, Magdalena; Bakšić, Darko; Lacković, Damir; Čop, Ana; Radolić, Vanja (Acta Carsologica, 2012)
We have performed measurements of the cave microclimate, water quality parameters and radon concentration to a depth of -1000 m in Velebita Cave system (Northern Velebit, Croatia). The results were analyzed as a function of the cave depth and geomorphological characteristics. Two different air temperature gradients were obtained, which can be attributed to a cave morphology and air circulation in the upper part of the pit. The water quality parameters show that the studied waters are poorly mineralized and are of weakly alkaline type. Water chemistry is probably predominantly controlled by the petrography of the bedrock (limestone) and the cave morphology. Water in the cave is not affected by pollution. The average value of radon concentration is rather low, much lower than in some other Croatian caves.